Complementary feeding with traditional and baby led weaning (BLW) methods - assessment of selected aspects of infant's diet - Agnieszka Białek-Dratwa; Alicja Michalak; Martina Grot; Karolina Krupa-Kotara (Kazimierz Wielki University, 2022)
Background: Infant nutrition is a topic of constant debate between parents and doctors. The recommendations themselves have been modified several times over the past 6 decades. Baby Led Weaning (BLW) method is gaining more and more popularity in infant nutrition during the period of expanding the infant menu. The main aim of the study was to evaluate selected aspects of dietary expansion in a group of their children, taking into account dietary expansion with the use of the traditional method and the BLW method. Material and method: An exploratory cross-sectional study was conducted in December 2021-January 2022 among a randomly selected sample of 523 mothers of children in infancy aged up to 12 months. Data for the study were collected anonymously using the CAWI method. The information collected from 500 women was considered for the final data analysis taking into account the inclusion and exclusion criteria. Results: 66.6% of the women surveyed (N=333) stated that their child is or was fed breast milk during the first six months. The child's diet was most often expanded with complementary meals after 6 months of age. This answer was indicated by 58.8% of respondents (N=294). 85.6% of the surveyed women (N=428) first introduced or intend to introduce vegetables to their diet. 13% of the respondents (N=65) introduced or planned to introduce vegetables and fruit at the same time. In the studied group of mothers the BLW method was not known or not used by 7 mothers (1.4%), 343 mothers used or intended to use the BLW method (68.6%), whereas 150 women knew the BLW method (30.0%), but did not use it or did not intend to use it during the expansion of their child's diet. Conclusions: The majority of mothers surveyed used the BLW method during the expansion of their children's diet, accepting the principle that it is the child who decides whether and how much to eat, and the parent who decides what and when the child eats.